Doses and number of applications of ethephon in sex reversal of zucchini squash flowers - Costa-Silva, Edgard Henrique [UNESP]; Torquato-Tavares, Aline; Alves-Ferreira, Tiago; Pascual-Reyes, Irais Dolores; Guimarães-Alves, Francielly Quitéria; Nascimento, Ildon Rodrigues-do (Universidad Autonoma Chapingo, 2020)
Ethylene can change the flowering pattern of some cucurbits, favoring the emergence of female flowers. The objective was to determine the influence of doses and number of ethephon applications in sex reversal of zucchini (Cucurbita pepo L.). The experiment was conducted in a 4 x 4 factorial arrangement, plus a control (natural flowering), the first factor being the ethephon doses (125, 250, 375 and 500 mg∙L-1) and the second the number of applications (1, 2, 3 and 4). Ethephon influenced the sexual expression of zucchini, but not enough to achieve complete sex reversal. The 500 mg∙L-1 dose provided the largest feminization for all applications. Ethephon might be a useful tool for zucchini breeding programs.
Dosis y número de aplicaciones de etefón en la reversión sexual de flores de calabacita
Keywords: Cucurbita pepo; Ethylene; Phytohormones; Sex expression in Cucurbits